Jenis Bentos Dan Plankton Pada Sungai Jemile Kabupaten Muara Enim Provinsi Sumatera Selatan - Putri Anggraini; Eva Suryani; Rita Puspasari; Moch. Zarwani; Yunita Panca Putri (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2024)
Rivers are vital freshwater ecosystems that play an essential role in maintaining environmental balance and supporting aquatic life. The benthic and planktonic communities serve as bioindicators of water quality and form integral components of the aquatic food web. This study aims to analyze the structure of benthos and plankton communities in the Jemile River, Muara Enim Regency, South Sumatra, and to evaluate their relationship with water quality parameters. The findings revealed the presence of Baetidae larvae, indicating clean and well-oxygenated waters, alongside Chironomidae, which tolerate organically enriched substrates. Among plankton, Brachionus was found as an indicator of eutrophic conditions, and Gyrosigma served as a primary producer. The diversity of organisms observed suggests habitat quality variations influenced by domestic, agricultural, and mining activities around the river. This study highlights the complex ecological dynamics of the Jemile River and underscores the need for continuous monitoring to support sustainable water resource management.